LAMELLAR ICHTHYOSIS (COLLODION BABY) - IGE, Paramarta; W, Retayasa; M, Kardana; AAGP, Wiraguna; S., Herman (Medicina, 2012)
The ichthyosis are a heterogeneous group of hereditary and acquired disorder of keratinization which affected the epidermis characterized by presence of visible scales on the skin surface in the absence of inflammation. It can occur as a disease limited to the skin or in association with abnormalities of other organ systems. Lamelar ihthyosis (LI) is one of two mayor autosomal recessive ichthyosis with an incidence of approximately one in 300,000. The diagnosis is based on clinical and pathologic finding. Infection is the most common complication, while prognosis of LI is depends on severity and complication of the disease. A case of lamellar ichthyosis in 0 day Balinese female baby was reported. The skin of the body was thick, plate-like appearance, scaling on the entire body, some of the thick skin was ruptured on chest and extremities. There were eclabium on the mouth and ectropion on the eyes. Histopathology examination showed hyperkeratosis without perivascular infiltration lymphocyte. The baby was given breast feeding, antibiotic, hydrocortisone cream and olium olivarum. The prognosis of the baby is good.
Keywords: ichthyosis, hyperkeratosis, baby